The Wind in the Willows: The Wild Wood - Mckie, Anne (Colour Library Books Ltd, 1991)
Adapted by Anne Mckie from Kenneth Grahame's original story.
Keywords: Juvenile literature-Animals-Classics- Friendship-Fiction